(untitled) (Journal of history, 2024)
The article describes the situation of the peoples who migrated to Kazakhstan during the develop ment of virgin and fallow lands, one of the largest reforms in the history of Kazakhstan of the twentieth century. Over the years of development of virgin and fallow lands, Kazakhstan has moved from various industries to the forefront in the Union republics. Also, during the migration process, there were visitors from other countries except the Union republics. This migration process was extensive both geographically and ethnically. The peoples of Russia, Ukraine, Belarus and other Union republics immigrated to Kazakhstan. During the period in which the virgin lands chronology entered, the movement of peoples was also directed in an external direction. The article uses monographs, articles, and statistical collections of researchers from the beginning of the Virgin Years to the present day. In addition, the migration process of the peoples of this period was compared with statistical data using the historical and comparative method. Key words: Kazakhstan; population census; statistics; development of virgin and fallow lands; demography; diaspora; migration.